An unusual case of pneumocephalus. (2nd November 2011) - Bhogal, P; Bhatnagar, G; Manieson, J; Booth, T; Prendergast, C
Abstract : The authors present an unusual cause of pneumocephalus in a previously fit and well female octogenarian who presented with acute onset altered level of consciousness and generalised weakness. Radiological imaging demonstrated widespread cerebritis with pneumocephalus and gas within the superior sagittal sinus. Blood culture grew Clostridium septicum, a virulent but rare organism that can infect normal tissues. The close association between C septicum and both haematological and bowel malignancies must be considered if this organism is cultured.